2021
DOI: 10.1177/0969733020976188
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 era healthcare ethics education: Cultivating educational and moral resilience

Abstract: The COVID-19 pandemic crisis has had profound effects on global health, healthcare, and public health policy. It has also impacted education. Within undergraduate healthcare education of doctors, nurses, and allied professions, rapid shifts to distance learning and pedagogic content creation within new realities, demands of healthcare practice settings, shortened curricula, and/or earlier graduation have also challenged ethics teaching in terms of curriculum allotments or content specification. We propose expa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 40 publications
1
11
0
1
Order By: Relevance
“…In addition, studies have reported that nurses were disappointed when they could not provide the necessary care for their patients, they felt ineffectual due to constant worries that they could not treat chronic patients, and though that they might endanger their health and that of their colleagues. Encountering too many deaths, patients dying in isolation and alone, fear of being infected themselves, the lack of protective equipment, infecting colleagues, families, friends due to lack of protective equipment or established protocols all threaten emotional and psychological well-being [31] . Nurses need information about Covid-19, healthcare ethics, nursing skills and psychological resilience strategies, ethical support, coping tools, and even therapy to prevent or alleviate the negative effects of these traumas on their psychosocial health, or to increase psychological resilience.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, studies have reported that nurses were disappointed when they could not provide the necessary care for their patients, they felt ineffectual due to constant worries that they could not treat chronic patients, and though that they might endanger their health and that of their colleagues. Encountering too many deaths, patients dying in isolation and alone, fear of being infected themselves, the lack of protective equipment, infecting colleagues, families, friends due to lack of protective equipment or established protocols all threaten emotional and psychological well-being [31] . Nurses need information about Covid-19, healthcare ethics, nursing skills and psychological resilience strategies, ethical support, coping tools, and even therapy to prevent or alleviate the negative effects of these traumas on their psychosocial health, or to increase psychological resilience.…”
Section: Discussionmentioning
confidence: 99%
“…This statement is consistent with Wald and Monteverde (2021). They report that educational resilience is vital in supporting and sustaining healthcare professional identity development and facilitating the progress of students' moral resilience and complexity, especially in times of pandemic [25].…”
Section: Second Stepmentioning
confidence: 99%
“…Resilience includes cognitive processes and has four dimensions, including self-efficacy. Planning, Self-control, Commitment, and perseverance include the following: young doctors must be present in various educational environments and support clinical and educational supervisors in enduring difficulties to help them develop personal and professional resilience [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…The need to move to online education and the impact this has on the anxiety levels of students was explored in a number of studies and students predominantly expressed anxiety about the future unfamiliarity and uncertainty. 24,[30][31][32][33][34][35][36][37][38][39] A review of how information was provided to students would be useful to establish the best platforms to share constant, and ongoing updates.…”
Section: Informationmentioning
confidence: 99%